Mitochondrial genome association study with peripheral arterial disease and venous thromboembolism. (September 2016) - Abrantes, Patrícia; Rosa, Alexandra; Francisco, Vânia; Sousa, Inês; Xavier, Joana M.; Oliveira, Sofia A.
Abstract: Background and aims: Peripheral arterial disease (PAD) and venous thromboembolism (VTE) are vascular traits sharing common modifiable and non-modifiable risk factors. These vascular pathologies have known nuclear-encoded genetic risk factors and the mitochondrial DNA may account for part of the missing heritability. To determine if PAD and VTE have a dual genetic control (mitochondrial and nuclear), we hereby investigated the association of mitochondrial DNA polymorphisms and haplogroups with these vascular traits. Methods: The association of mitochondrial single nucleotide polymorphisms (mtSNPs) and haplogroups was tested in 1652 PAD cases and 1629 controls from the eMERGE PAD genome-wide association study (GWAS), and 1241 VTE cases and 1278 controls from the GENEVA GWAS of venous thrombosis (dbGaP accession numbers phs000203.v1.p1 and phs000289.v2.p1, respectively). Results: 66 and 72 mtSNPs passed quality control filters and were tested for association with PAD and VTE, respectively. Significant evidence of population stratification could not be detected in both datasets. Three mtSNPs (m.477T > C, m.9667A > G, and m.10915T > C) were nominally associated (3.01 × 10 −3  ≤  p a  ≤ 3.96 × 10 −2 ) with PAD in the logistic regression adjusted for confounding factors, and m.11914G > A was nominally associated ( p a  = 4.14 × 10 −2 ) with VTE. None of the nine major mitochondrial haplogroups were associated with either PAD or VTE. Conclusion: Unlike other vascular diseases such as stroke and diabetes, these results suggest that common mitochondrial variants individually or in combination do not play a major role in PAD and VTE susceptibility. Highlights: First association study of the mitochondrial genome with PAD and VTE. m.477T > C, m.9667A > G, and m.10915T > C were nominally associated with PAD. m.11914G > A was nominally associated with VTE. No haplogroups were associated with PAD or VTE. Common mitochondrial variants do not play a major role in PAD and VTE risk.